Effect of Tax Amnesty and Taxpayer Awareness of Taxpayer Compliance: Study at Jakarta Cilandak Primary Tax Service Office - Awaloedin, Dipa Teruna; Hasanudin; Widarta, I Gede; Abbas, Asyari; Karyatun, Subur; Pradini, Gagih (CV ODIS, 2024)
This study aims to determine whether there is an influence between tax amnesty (tax amnesty) and taxpayer compliance and whether there is an influence between taxpayer awareness and taxpayer compliance. The research method used is the Incidental Sampling method. Primary data was collected by distributing questionnaires to 100 respondents. The data analysis used is statistical analysis in the form of multiple linear regression tests. Data is processed using SPSS version 24 for Windows. Based on the results of the study, it show that Tax Amnesty (Tax Amnesty) has a positive and significant effect on Taxpayer Compliance. Likewise, Taxpayer Awareness has a positive and significant impact on Taxpayer Compliance.